Lessons learnt from a process evaluation of an exercise intervention in patients treated with autologous stem cell transplantation. (27th September 2017) - Persoon, S.; Chinapaw, M.J.M.; Buffart, L.M.; Brug, J.; Kersten, M.J.; Nollet, F.
Abstract : This paper describes the process evaluation of an 18‐week supervised exercise programme in 50 patients treated with high‐dose chemotherapy followed by autologous stem cell transplantation. The intervention included 30 exercise sessions with six resistance exercises and interval training. We evaluated the context, dose delivered and received, and patients' and physiotherapists' satisfaction with the intervention. Ninety‐two per cent of the patients trained within 15 km of their home address, with an average session attendance of 86%. Most patients trained at the prescribed intensity for four of the six resistance exercises, but the dose delivered and received of the two remaining resistance exercises and interval training could not be determined. Both patients and physiotherapists highly appreciated the programme (score of 8.3 and 7.9 out of 10 respectively). This process evaluation provided valuable lessons for future trials: (1) It is possible to deliver supervised exercise training to this patient group in local physiotherapy practices; (2) to determine dose received all intervention components should be standardised; and (3) to optimise data collection, all study materials should be tested more extensively prior to the start of the intervention.